EFEKTIFITAS PELAYANAN PEMBERIAN KREDIT BRIGUNA PADA PT ASURANSI BRI LIFE JAKARTA - Purwitasari, Maria Evy; Meilandri, Detti; Minggu, Minggu; Purnomo, D; Riyanto, Aris (POLITEKNIK LP3I JAKARTA, 2023)
This study discusses an analysis of the covering process for briguna credit life insurance products carried out by PT. BRI Life Insurance. This study aims to understand in depth the covering process carried out by these companies in providing life insurance products related to Briguna. The methodology used in this research is direct observation at PT. BRI Life Insurance, interviews with related staff, and documentation studies. The data obtained was analyzed using a descriptive approach to identify and understand the steps involved in the process of covering BRIGUNA life insurance products. The results showed that the process of covering BRIGUNA life insurance products at PT. BRI Life insurance involves several stages. Each stage in lending must be carried out sequentially starting from credit application, credit analysis and decision, to the final stage, namely credit realization and documentation. Keywords: Analysis, Process, Covering.